2022
DOI: 10.1177/00220345221112333
|View full text |Cite
|
Sign up to set email alerts
|

Automatic 3-Dimensional Cephalometric Landmarking via Deep Learning

Abstract: The increasing use of 3-dimensional (3D) imaging by orthodontists and maxillofacial surgeons to assess complex dentofacial deformities and plan orthognathic surgeries implies a critical need for 3D cephalometric analysis. Although promising methods were suggested to localize 3D landmarks automatically, concerns about robustness and generalizability restrain their clinical use. Consequently, highly trained operators remain needed to perform manual landmarking. In this retrospective diagnostic study, we aimed to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
(52 reference statements)
2
19
0
2
Order By: Relevance
“…The data showed that our method was more accurate in identifying the mandibular parts than previous studies. 5,11,12 However, the error of our points was similar to or even better than theirs. In addition, the manual measurements process took 15 minutes, but we only needed 16 seconds.…”
Section: Three-dimensional Modelsupporting
confidence: 74%
See 1 more Smart Citation
“…The data showed that our method was more accurate in identifying the mandibular parts than previous studies. 5,11,12 However, the error of our points was similar to or even better than theirs. In addition, the manual measurements process took 15 minutes, but we only needed 16 seconds.…”
Section: Three-dimensional Modelsupporting
confidence: 74%
“…Three-dimensional CT-based cephalometric imaging has recently been widely used to comprehensively evaluate carried out relying on manual measurements, which is time-consuming, labor-intensive, and relies heavily on the operator’s judgment 13 . In recent years, some scholars have begun to carry out deep learning algorithms based on fully automatic 3D cephalometric marking points, achieving relatively good accuracy and good results 5–12 . By automating measurement, time, and effort can be significantly reduced, lowering the burden on clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…It is very versatile. Some attempts to utilize deep learning for automatic 3D landmark prediction have been reported [45,49,51,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…A knowledge-based method [43] was reported in 2015. Some kinds of learning based methods [44][45][46][47][48][49][50][51] have been reported. In our experience with 2D cephalograms [27,28], multi-phased deep learning system was able to predict coordinate values in high precision.…”
Section: Introductionmentioning
confidence: 99%
“…To use such data fully and appropriately, there has been a concomitant explosion in data analytics, notably including the application of AI. This special issue highlights the application of AI for developing clinically relevant tools, for example, evaluating factors contributing to the long-term survival of root canal treatments using data from the National Dental Practice Based Research Network ( Thyvalikakath et al 2022 ), the diagnosis of oral squamous cell carcinoma ( Yanget al 2022 ), automated 3-dimensional (3D) cephalometric landmarking ( Dot et al 2022 ), the prediction of 3D postorthodontia facial changes in adults ( Park et al 2022 ), the predictive classification of tooth removal procedures ( de Graaf et al 2022 ), and the association of components of computer-aided design/computer-aided manufacturing resins with clinical outcomes ( Li et al 2022 ).…”
mentioning
confidence: 99%